2015
DOI: 10.5296/ijafr.v5i1.7746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Stability of the Financial Ratios of Jordanian Industrial Companies

Abstract: The purpose of the study was to identify if the financial ratios of Jordanian industrial companies remained stable across sector and over time. The study used six financial ratios from fifty-six companies across six sectors with financial information from 2010 to 2014. A two way multivariate analysis of variance was performed to identify the stability of the ratios across the sectors and over the time. The results of the study showed that the financial ratios which showed some difference across sector were EBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The results of the study by Rumman (2015), indicated that the Earnings before Interest and Tax, Current Assets Turnover and Cash Flow to Total Assets were financial ratios which were different from industry to industry. When it comes to variations between the financial ratios over time there were no changes as per the study.…”
Section: Literature Review Prior Studies On Financial Ratio Componementioning
confidence: 97%
See 1 more Smart Citation
“…The results of the study by Rumman (2015), indicated that the Earnings before Interest and Tax, Current Assets Turnover and Cash Flow to Total Assets were financial ratios which were different from industry to industry. When it comes to variations between the financial ratios over time there were no changes as per the study.…”
Section: Literature Review Prior Studies On Financial Ratio Componementioning
confidence: 97%
“…As per Rumman (2015), financial ratios can be used in order to financially ascertain Performance of companies. This ratio study facilitates companies to realize their financial strengths and weaknesses.…”
Section: Prior Studies On Factors Affecting To Profitabilitymentioning
confidence: 99%